P511 Disease-specific risk factors for malnutrition development in IBD. (27th May 2021) - Einav, L; Hirsch, A; Ron, Y; Aviv Cohen, N; Anbar, R; Lahav, S; Maharshak, N; Fliss Isakov, N
Abstract: Background: Patients with inflammatory bowel diseases (IBD) are at risk of malnutrition, which is associated with considerable disease related complications. Most available screening tools for malnutrition risk such as the malnutrition universal screening tool (MUST), do not incorporate malnutrition-promoting characteristics of IBDs. Therefore, we aimed to detect disease-specific risk factors for malnutrition development in IBD, which may be incorporated in future malnutrition screening tools. Methods: A retrospective case-control study, in which detailed information regarding IBD patients treated at the IBD clinic of the Tel-Aviv Medical Center between 2010–2020 was collected. Cases were patients who developed malnutrition between clinic visits (defined as BMI≤18.5/ weight loss ≥5% of body weight during 3 months/≥10% of body weight during 6 months) and controls were those who maintained a normal nutritional status. Cases and controls were matched by age, gender, disease and disease duration. Data was collected from medical files included reported medical history, clinical manifestations of disease, disease activity, and nutritional status including MUST evaluation during clinic visits. The association between the clinical data and malnutrition development was evaluated using a logistic regression model, with adjustment for MUST components: weight loss of ≥5% of body weight and multiple (≥2) reasons for inadequate nutritional intake. Results: We collected data from 118 IBD patient (cases, n=59 and controls n= 59, Crohn's disease n=76, ulcerative colitis n=28, pouchitis patients n=14). All patients were at normal nutritional status at baseline. Patients were followed for a period of 6.2±3.0 months during which, cases lost 5.3±2.3 kg (10.4±4.8 % body weight) and controls gained 0.2±2.3 kg )0.2±3.5 % body weight) (p<0.001). MUST screening misclassified 34% of cases as low risk for malnutrition. Development of malnutrition was positively associated with baseline endoscopic disease activity [Odds ratio (OR)=6.06, 95% Confidence interval (CI) 1.91–19.18], repeated physician/nurse clinic visits ≥4/year (OR=5.26, 1.20–22.98), and negatively associated with advanced therapy (biologics and small molecules) (OR=0.151, 0.03–0.70), and BMI at baseline (OR=0.24, 0.13–0.44). The fit of this model was evaluated by an area under the curve of AUC=0.961 CI 0.93–0.99, p<0.001. Conclusion: Current tools for prediction of malnutrition among IBD patients are not sensitive enough. Parameters, such as increased disease activity should prompt nutritional assessment among patients to prevent mal-nutrition. The importance of these findings should be evaluated in prospective studies.